Integrated Report Disclosure in ESG Index Companies on the Indonesia Stock Exchange: Its Impact on the Cost of Equity Capital - Cahyani, Selvi Regita; Permatasari, Ika (JOURNAL OF MANAGEMENT, ACCOUNTING, GENERAL FINANCE AND INTERNATIONAL ECONOMIC ISSUES, 2025)
With the growing emphasis on sustainability and transparency in capital markets, the importance of analyzing the influence of integrated reporting on equity financing costs becomes a crucial topic for research. This study aims to examine the effect of Integrated Report disclosure on equity capital costs, against the backdrop of companies' needs in the era of globalization, which no longer focus solely on financial aspects but also on sustainability aspects. The Integrated Report approach serves as a strategy to communicate these aspects comprehensively, including in the process of creating value for stakeholders, which directly impacts equity capital costs. Using multiple linear regression method, this study explores the relationship between integrated report and cost of equity capital, with a sample of companies incorporated in the Environment, Social, and Governance (ESG) index on the Indonesia Stock Exchange (IDX) for the period 2019-2023. The results showed that the integrated report has a positive effect on the cost of equity capital. This shows that the implementation of an integrated report requires considerable time and cost at the beginning, thus requiring higher capital. Ultimately, this research is expected to assist companies in reviewing the quality of reporting from both financial and non-financial information, so as to increase investor confidence with better transparency.